JAVANESE WEDDING TRADITIONS: BETWEEN HERITAGE AND ARAB INFLUENCE - Maghfiroh Fitri Ananta; Nur Hasaniyah (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2025)
This study examines the dynamics of Javanese wedding traditions that have retained their cultural essence despite acculturation with Arab culture and modernization. A qualitative, descriptive-analytical approach was used to observe traditional Javanese wedding ceremonies and how they have changed in response to external cultural influences. Data were obtained through direct observation of wedding ceremonies in Java and analyzed using triangulation techniques. The results show that, while Javanese weddings maintain traditional values such as togetherness and family harmony, elements of Javanese culture have been modified to align with Islamic values. For example, the accompaniment of the bride and groom with gamelan music and traditional dodot clothing has been replaced with sholawat and tambourines. The study also revealed changes in guest seating arrangements, with some families adopting the Arab tradition of separating male and female guests. This study provides insight into how Javanese culture remains alive and relevant by maintaining traditions while adapting to modernization and outside cultural influences. It also provides an example of cultural flexibility in the face of changing times.